2020
DOI: 10.9758/cpn.2020.18.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the Deltoid Muscle Injection of Aripiprazole Long-acting Injectable in the Patients with Schizophrenia

Abstract: Objective: To improve poor medication adherence in schizophrenic patients, long-acting injectable (LAI) antipsychotics are used. However, it has not yet become common in Japan. Recently, aripiprazole LAI was approved for alternative injection into the deltoid muscle in addition to the gluteal muscle. The acceptance for the proposal to switch from gluteal to deltoid injections of aripiprazole LAI was investigated. Methods: The subjects were 32 outpatients with schizophrenia who had continuously received aripipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… 1 , 2 , 3 , 4 , 5 Antipsychotic monotherapy (APM) has been the gold standard for schizophrenia treatment, 2 , 6 , 7 , 8 , 9 however, empirically 10 to 60% of schizophrenia patients respond poorly or only partially to APM in real practice. 10 , 11 , 12 , 13 , 14 Based on recent individual patient data from randomized controlled trials (RCTs), 15 approximately 2 out of 10 patients (19.8%) starting APM failed to show any symptom improvement after acute phase treatment for more than 4 weeks, however, it increased up to 4–7 out of 10 patients (43–67%) when applying different criteria for response to AP therapy (25/50% more reduction in Positive And Negative Syndrome Scale, PANSS).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 Antipsychotic monotherapy (APM) has been the gold standard for schizophrenia treatment, 2 , 6 , 7 , 8 , 9 however, empirically 10 to 60% of schizophrenia patients respond poorly or only partially to APM in real practice. 10 , 11 , 12 , 13 , 14 Based on recent individual patient data from randomized controlled trials (RCTs), 15 approximately 2 out of 10 patients (19.8%) starting APM failed to show any symptom improvement after acute phase treatment for more than 4 weeks, however, it increased up to 4–7 out of 10 patients (43–67%) when applying different criteria for response to AP therapy (25/50% more reduction in Positive And Negative Syndrome Scale, PANSS).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies presented evidence that patients preferred deltoid injections over gluteal injections, perceiving the deltoid site to be less embarrassing. 47 , 70 However, another study found no statistically significant difference in perceived level of shame between a group that switched from gluteal to deltoid administration and a group that did not (p=0.436). 46 Two studies found that health professionals believe deltoid injections are less stigmatising than gluteal injections.…”
Section: Resultsmentioning
confidence: 97%
“… 46 , 47 , 70 Among these, two studies reported that embarrassment was the reason for a moderate proportion of patients (~40% in both studies), 47 , 70 while the third reported only a small proportion of patients with a “meaningful level of shame”. 46 Another study noted that the patients who reported less shame with deltoid injections were all women; 47 it may therefore be relevant for future studies to investigate gender-based differences in antipsychotic-related stigma. Two international surveys of nurses reported that the majority of nurses agreed with statements indicating that deltoid injections reduce stigma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations